Trafficking of Mycobacterium tuberculosis Envelope Components and Release Within Extracellular Vesicles: Host-Pathogen Interactions Beyond the Wall - Layre, Emilie (Frontiers in Immunology, 2020)
Mycobacterium tuberculosis (Mtb) produces an extremely diverse lipidome endowed with potent immunomodulatory properties. As components of the bacillus envelope, Mtb (glyco)lipids, lipoproteins or lypoglycans interact with pattern recognition receptors expressed at the host cell surface, hence contributing in different ways to the bacillus recognition, phagocytosis and to immune responses modulation. However, Mtb lipids are not only encountered at the bacillus-host direct contact but can act remotely from the bacillus envelope. Indeed, Mtb lipids are also released from the bacillus envelope and are detected in different compartments such as the infected cells endocytic pathway or in extracellular vesicles produced by the bacillus itself or by infected cells. Characterising the trafficking of Mtb lipids is of main importance for our understanding of their role in host-pathogen interactions and consequently on their potential use as vaccine components. This review aims at summarizing the state of knowledge on the nature of Mtb lipids released from the bacillus envelope within vesicles, its trafficking and interaction with host cells and the remaining black holes.